Extraction and selective precipitation of metal ions from LiCoO2 cathodes using citric acid. - Cerrillo-González, María del Mar; Paz-García, Juan Manuel; Muñoz-Espinosa, María; Rodríguez-Maroto, José Miguel; Villén-Guzmán, María Dolores (Elsevier, 2023)
The most common methods for recycling Lithium-Ion Batteries use strong mineral acids and hydrogen peroxide. Alternative acids and reducing agents are currently being studied to reduce the environmental impact of these batteries recycling processes. This research provides a practical pathway for recycling batteries using citric acid as a sustainable lixiviant. The combination of citric acid and copper as extractant and reductant agents, respectively, to selectively recover lithium and cobalt from LiCoO2 has been studied. Leaching with 2 M citric acid and 70 °C in the presence of copper resulted in a recovery of nearly 100 % Li and around 81 % Co, contained in the liquid phase and the solid precipitate formed during the experiments. Cobalt solubility experiments and solid characterization were performed to understand further the formation of cobalt-citrate solid species detected. Experimental and theoretical results suggest that the precipitate could be identified as CoHCitrate, associated with the selective recovery of cobalt from LiCoO2. Results obtained in this work indicate that citric acid could be used not only as an extractant agent but also as a precursor to precipitate metals from LIBs, improving the efficiency and selectivity of recycling processes.
Keywords: Pilas de litio; Reciclado; Lithium-ion batteries; Recycling; Leaching; Citric acid; Copper; Citrate-cobalt complexes